Anti-inflammatory deficiencies in neutrophilic asthma: reduced galectin-3 and IL-1RA/IL-1β. Issue 1 (December 2015) - Gao, Peng; Gibson, Peter; Baines, Katherine; Yang, Ian; Upham, John; Reynolds, Paul; Hodge, Sandra; James, Alan; Jenkins, Christine; Peters, Matthew; Zhang, Jie; Simpson, Jodie
Abstract Background Galectin-3 (gal-3), a member of the β-galactoside-binding animal lectins, is involved in the recruitment, activation and removal of neutrophils. Neutrophilic asthma is characterized by a persistent elevation of airway neutrophils and impaired efferocytosis. We hypothesized that sputum gal-3 would be reduced in neutrophilic asthma and the expression of gal-3 would be associated with other markers of neutrophilic inflammation. Methods Adults with asthma (n = 80) underwent a sputum induction following clinical assessment and blood collection. Sputum was dispersed for a differential cell count and ELISA assessment of gal-3, gal-3 binding protein (BP), interleukin (IL)-1β, IL-1 receptor antagonist (RA), IL-8 and IL-6. Gal-3 and gal-3BP immunoreactivity were assessed in mixed sputum cells. Results Sputum gal-3 (median, (q1, q3)) was significantly reduced in neutrophilic asthma (183 ng/mL (91, 287)) compared with eosinophilic (293 ng/mL (188, 471), p = 0.021) and paucigranulocytic asthma (399 ng/mL (213, 514), p = 0.004). The gal-3/gal-3BP ratio and IL-1RA/IL-1β ratio were significantly reduced, while gal-3BP and IL-1β were significantly elevated in neutrophilic asthma compared with eosinophilic and paucigranulocytic asthma. Conclusion Patients with neutrophilic asthma have impairment in anti-inflammatory ratio of gal-3/gal-3BP and IL-1RA/IL-1β which provides a further framework for exploration into pathologic mechanisms of asthma phenotypes.